A numerical model of a linear compressor for household refrigerator. (5th November 2021) - Zhu, Zhennan; Liang, Kun; Li, Zhaohua; Jiang, Hanying; Meng, Zhongwei
Highlights: A comprehensive numerical model of a linear compressor was established. Experiments were conducted to validate the numerical model. The measured and predicted piston displacement, current and shaft force agree well. The model is capable of modulating the cooling capacity for high efficiency operation. Abstract: Linear compressor is more efficient than conventional reciprocating compressor due to the absence of a crank mechanism. It can also realize capacity modulation, compactness and oil-free operation. A comprehensive numerical model of a linear compressor consisting of a thermodynamic model describing the in-cylinder pressure and temperature, a mechanical dynamics model describing movement the piston and valves and an electrical model describing the interaction of the voltage, current and back electromotive force of the linear motor was established to predict the compressor performance and to help achieve inherent capacity modulation. Experiments were conducted to validate the model using a prototype moving magnet linear compressor and remarkable accuracy is obtained. The measured and predicted piston displacement, current and shaft force agree well with the maximum error less than 10%. The predicted power factor, power consumption, stroke, mass flow rate and CoP show mean absolute percentage errors of 0.8%, 13.3%, 3.9%, 9.2% and 9.0%, respectively. As predicted, the resonant frequency can lead to lowest power consumption as well as the highest power factor and motor efficiency. At pressure ratio of 3.0, when the piston stroke increases by 1 mm, the mass flow rate increases by 0.66 g/s while the cooling capacity increases by 77.2 W. This can indicate the possibility of inherent capacity modulation.